Macedonians of Islamic Religion in the Context of Identity Theories - Kulavkova, Katica (European Scientific Journal, ESJ, 2018)
In line with the theories of variability, fluctuation and instability of ethno-cultural identities, this paper deals with some sensitive issues surrounding the creation of new (sub-ethnic and sub-cultural) microidentities within one nation, in this case within the Macedonian nation. The research focuses on the initiative for declaring one part of the Macedonian nation, the Macedonians of Islamic religion, to be a separate ethnic group in 2011. It analyses the regional and historical background from which this initiative originated, mostly as an echo of the multicultural strategies and policies in the European and international context. It shows how the unstable politics destabilized the already fragile and fluctuating identity of this group toward an identity of resistance or even heresy, inspite of having preserved their primary Slavic linguistic and cultural identity. The paper argues that the Macedonians of Islamic religion are a part of the Macedonian social, cultural and religious reality and should therefore be recognized as a specific cultural-religious community within the Macedonian national entity. This issue is seen as very important in the present context, since the Macedonian identity is preasured and relativized itself. The paper underlines that the Macedonian national identity is inclusive, layered, more general and complex than its religious factor. Therefore this researcher proposes inclusive state policies for all Macedonians regardless of religious affiliation, inclusive civilizational strategies with inter-connective spiritual values (inter-religious palimpsests and symbiosis) and inclusive state secular strategies as protection against religious radicalisms, atavisms and conflicts.